Perfil químico, análise físico-química e atividade antioxidante de Capsicum chinense Jacq (Solanaceae) cultivada na cidade de Boa Vista, Roraima - Marangon, Cristiane (2016)
Peppers are widely consumed in the state of Roraima, both by indigenous communi-ties, roraimenses and as the population migrated to the state. They are widely used in local cuisine, mainly by native peoples of the region, preparing a known broth pep-per base, called "damorida". Historically the oldest data peppers consumption date from about 9000 years this year and is a result of archaeological explorations in Te-huacan, Mexico. Research in the area of hot spices like pepper has been growing and expanding as the need to know more of this condiment. Its application in medi-cine is being increasingly studied, and is already used as analgesic, helps in the fight against prostate cancer, powerful antioxidant, among others. Since there is a great lack of studies with Capsicum peppers in the state where there is so much consump-tion, this study evaluated the physical and chemical composition (pH, ash content, humidity, fat, protein and vitamin C), antioxidant activity and It characterizes the fixed oil of pepper fruit-eye fish (Capsicum chinense Jacq), produced at Embrapa (Brazili-an Agricultural research). Analyses were performed in a specialized laboratory in the same company, and the following results were found pH: 4.98 ± 0.01; ash: 1.15 ± 0.01%; humidity: 82.6 ± 0.03%; lipid: 2.22 ± 0.20%; protein: 1.50 ± 0.06 % and vita-min C (ascorbic acid): 31.66 mg/ 100g ± 4.40. As for the antioxidant activity by the DPPH method, the fixed oil pepper Fisheye presented antioxidant activity, but with an IC50 of 2861.2 μg/ml-1. Through infrared spectrometric technique it was possible to detect the following functional groups: Aliphatic C-H stretch at approximately 2920 the 2938 cm-1, stretch C=O 1690 at 1640 cm-1 unsubstituted amides, N-H angular deformation in 1520 cm-1, characteristic CH2 fatty acids in 1438 cm-1 and a band at 1080 cm-1 which shows characteristics of an ether. A total of 19 chemical constitu-ents were detected by GC-MS method, among which 2,3-butanediol (37.13%), 2-heptenal (13.94%), palmitic acid (5.79%) and natural Capsaicin (13.10%) were the majority. The analysis of the fixed oil by 1H NMR showed signs of protons consistent with vegetable oils in general, showing saturated in its higher composition, and unfit for human consumption.